On the stability of antimony doped tin oxide supports in proton exchange membrane fuel cell and water electrolysers. Issue 6 (29th April 2019) - Jiménez-Morales, Ignacio; Cavaliere, Sara; Dupont, Marc; Jones, Deborah; Rozière, Jacques
Abstract : This study on bare and catalysed Sb–SnO2 electrospun tubes allowed to determine the potential window for its optimal utilisation as electrocatalyst support in PEM fuel cells and water electrolysers: the stability of the oxide strongly depends on the existing surface segregation of Sb. Abstract : The electrocatalyst support antimony doped tin oxide (ATO) was investigated at low and high potentials with ex situ and in situ electrochemical techniques to assess its stability in proton exchange membrane fuel cell (PEMFC) and water electrolysis (PEMWE) operating conditions.